2022
DOI: 10.7554/elife.73718
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of muscle strength in a mouse model for congenital myopathy treated with HDAC and DNA methyltransferase inhibitors

Abstract: To date there are no therapies for patients with congenital myopathies, muscle disorders causing poor quality of life of affected individuals. In approximately 30% of the cases, patients with congenital myopathies carry either dominant or recessive mutations in the RYR1 gene; recessive RYR1 mutations are accompanied by reduction of RyR1 expression and content in skeletal muscles and are associated with fiber hypotrophy and muscle weakness. Importantly, muscles of patients with recessive RYR1 mutations exhibit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Thus, epigenetic modifying enzymes may constitute a valid therapeutic target for RYR1-RM. Consistent with this, inhibiting DNA methyltransferases and class II histone deacetylases improves muscle function in a mouse model of recessive RYR1-RM [60], providing a proof-of-concept for the pharmacological treatment of patients with CM linked to recessive RYR1 variants. In recently published work, the Zorzato/Treves team investigated the expression of different transcripts, including those encoding epigenetic enzymes, in human muscle biopsies from patients with genetically diverse CMs.…”
Section: Ryr1 Genetics and Variant Classificationsupporting
confidence: 52%
“…Thus, epigenetic modifying enzymes may constitute a valid therapeutic target for RYR1-RM. Consistent with this, inhibiting DNA methyltransferases and class II histone deacetylases improves muscle function in a mouse model of recessive RYR1-RM [60], providing a proof-of-concept for the pharmacological treatment of patients with CM linked to recessive RYR1 variants. In recently published work, the Zorzato/Treves team investigated the expression of different transcripts, including those encoding epigenetic enzymes, in human muscle biopsies from patients with genetically diverse CMs.…”
Section: Ryr1 Genetics and Variant Classificationsupporting
confidence: 52%
“…Home-cage behaviour and social interaction phenotypes are also common between Cav2.3 phosphomutant and CDKL5 KO mice 46, 71 . The deficits observed in voluntary wheel in Cav2.3 phosphomutants could be indicative of mild hypotonia 82, 83 . Importantly, these phosphomutant mouse phenotypes mirror human clinical manifestations of CDD, arguing that slowed inactivation and enhanced cholinergic modulation of unphosphorylated Cav2.3 may contribute to these symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…Cav2.3 S15A mice recapitulate the reduced home-cage locomotion behaviour in CDKL5 KO mice 48,73 . The deficits observed in voluntary wheel in Cav2.3 phosphomutants could be indicative of mild hypotonia 86,87 . Finally, reduced social interaction in Cav2.3 phosphomutant mice was also observed in CDKL5 KO mice 15,48,73 and inhibitory neuron specific deletion of CDKL5 88 .…”
Section: Discussionmentioning
confidence: 97%
“…The reason for the selective effect of the homozygous A4329D mutation in slow-twitch fibers is not known; the authors suggested that a different epigenetic regulation of fast- versus slow-twitch muscle fibers may account, at least in part, for these differences ( Elbaz et al, 2020 ). Indeed, an increase in histone deacetylase (HDAC) was observed in soleus muscle of Ryr1 A4329D mice and, interestingly, in muscles from patients carrying recessive RYR1 mutations ( Zhou et al, 2006 ; Rokach et al, 2015 ; Ruiz et al, 2022 ). Although the correlation between expression of mutant RYR1 channels and epigenetic changes is not clear, the use of an inhibitor of HDAC and DNA methylase significantly improved muscle strength and RYR1 expression ( Ruiz et al, 2022 ).…”
Section: Mutations Causing a Reduction In Ryr1 Protein Content: Relat...mentioning
confidence: 99%
“…Indeed, an increase in histone deacetylase (HDAC) was observed in soleus muscle of Ryr1 A4329D mice and, interestingly, in muscles from patients carrying recessive RYR1 mutations ( Zhou et al, 2006 ; Rokach et al, 2015 ; Ruiz et al, 2022 ). Although the correlation between expression of mutant RYR1 channels and epigenetic changes is not clear, the use of an inhibitor of HDAC and DNA methylase significantly improved muscle strength and RYR1 expression ( Ruiz et al, 2022 ).…”
Section: Mutations Causing a Reduction In Ryr1 Protein Content: Relat...mentioning
confidence: 99%